2020
DOI: 10.13171/mjc10502005141394aa
|View full text |Cite
|
Sign up to set email alerts
|

Tin corrosion inhibition by molybdate ions in 0.2 M maleic acid solution: Electrochemical and surface analytical study

Abstract: <p>The inhibition efficiency of molybdate ions (MoO<sub>4</sub><sup>2-</sup>) against tin corrosion in 0.2 M Malic acid has been studied using electrochemical (DC and AC) and surface analytical methods (SEM and EDX). The electrochemical polarization curves revealed the presence of an active/passive transition of the tin electrode. The electrochemical impedance measurements (EIS) confirmed the benefic effect of increasing MoO<sub>4</sub><sup>2-</sup> concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Some investigations demonstrated similar behavior by investigating the mild steel corrosion inhibition by HPO 4 2− ions in NaCl solution of [10]. In an earlier contribution, it was shown that in a contradictory tendency, the addition of MoO 4 2− ions to a synthetic medium stimulates the dissolution of tinplate regardless of raising the temperature [18].…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Some investigations demonstrated similar behavior by investigating the mild steel corrosion inhibition by HPO 4 2− ions in NaCl solution of [10]. In an earlier contribution, it was shown that in a contradictory tendency, the addition of MoO 4 2− ions to a synthetic medium stimulates the dissolution of tinplate regardless of raising the temperature [18].…”
Section: Resultsmentioning
confidence: 80%
“…Several investigations reported the low toxicity and eco‐friendly suitability of molybdate anions (MoO 4 2− ), as tin corrosion inhibitors in different media [16, 17]. In a previously published contribution, we demonstrated that molybdate anions hinder the pitting corrosion of tinplate in a synthetic media analogous to industrial water comprising chloride, sulfate, and hydrogen carbonate ions; the pitting phenomenon decelerated and simultaneously accelerate the uniform corrosion by involving the untinned process [18].…”
Section: Introductionmentioning
confidence: 74%